First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Genetic diversity of the Atacama Desert shrub Huidobria chilensis in the context of geography and climate - K. Bechir Ferchichi; T. Böhnert; B. Ritter; D. Harpke; A. Stoll; P. Morales; S. Fiedler; F. Mu; J. Bechteler; C. Münker; M.A. Koch; T. Wiehe; et al. (Global and Planetary Change, 2024)

Adsorptive behavior of the rare earth elements Ce and La on a soybean pod derived activated carbon: Application in synthetic solutions, real leachate and mechanistic insights by statistical physics modeling - Raphael F. Pinheiro; Alejandro Grimm; Marcos L.S. Oliveira; Julien Vieillard; Luis F.O. Silva; Irineu A.S. De Brum; Éder C. Lima; Mu. Naushad; Lotfi Sellaoui; Guilherme L. Dotto; Glaydson S. dos Reis (Chemical Engineering Journal, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Resistance of Salmonella and Campylobacter Species to Antimicrobial Agents - B. Mirelis; G. Prats; T. Llovet; C. Muoz; F. Navarro (European Journal of Clinical Microbiology & Infectious Diseases, 1999)